Revisiting the Relationship between Trade Liberalization and Taxation - Rabah Arezki; Alou Adesse Dama; Gregoire Rota-Graziosi (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper explores the dynamic effects of trade liberalization on tax revenue using a worldwide panel dataset. Results point to statistically significant negative effect of liberalization on (non- resource) tax revenues in the short term and no significant effect in the medium term. Liberalization also alter the tax structure tilting revenues toward indirect taxes away from direct ones. Economies which have implemented value added taxes prior to liberalization have mitigated its negative effects on tax revenues. The evidence is supportive of the complementarity role of state capacity to reap the benefits of liberalization.
Keywords: H20; H87; F13; 330; tax; tax structure; openness; liberalization; natural resources